2016
DOI: 10.3390/en9030191
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Increased Irrigation Demands: What Is Left for Hydropower Generation? Results from Two Semi-Arid Basins

Abstract: Abstract:In this study, we have modelled the effect of climate change and increased irrigation withdrawals on the available water for hydropower production in two semi-arid river basins, i.e., Kizilirmak (Turkey) and Devoll (Albania), and the role of the reservoirs. The combined effect of climate change and extended irrigation withdrawals will overall lead to reduced runoff in the rivers, according to our simulations. The changes will be most dramatic at Kizilirmak, reducing the water available for hydropower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Climate projections have been used to estimate water demand for future irrigation (Gondim et al, 2012;Bakken et al, 2016), which are estimated to increase between 40 and 250% depending on the crop at the end of this century. The increased requirements have been ascribed to reduce water availability in the growing seasons, evapotranspiration and changes in crop phenology (Woznicki et al, 2015;Sloat et al, 2020;Dai et al, 2020).…”
Section: Increased Irrigationmentioning
confidence: 99%
“…Climate projections have been used to estimate water demand for future irrigation (Gondim et al, 2012;Bakken et al, 2016), which are estimated to increase between 40 and 250% depending on the crop at the end of this century. The increased requirements have been ascribed to reduce water availability in the growing seasons, evapotranspiration and changes in crop phenology (Woznicki et al, 2015;Sloat et al, 2020;Dai et al, 2020).…”
Section: Increased Irrigationmentioning
confidence: 99%
“…Haddeland et al (2006) found that the streamflow in Colorado and Mekong river basins decreased by 37% and 2.3%, respectively, in the analyzed period. Bakken et al (2016a) found large flow reductions in Kizilirmak river basin due to irrigation withdrawals, in particular in the middle and lower parts. The results from Devoll river basin in Albania showed a different picture as only limited effects could be seen due to irrigation, which to a large extent was explained by the collapse in the agricultural sector in the early 1990's (Bakken et al, 2016a).…”
Section: Irrigationmentioning
confidence: 90%
“…Bakken et al (2016a) found large flow reductions in Kizilirmak river basin due to irrigation withdrawals, in particular in the middle and lower parts. The results from Devoll river basin in Albania showed a different picture as only limited effects could be seen due to irrigation, which to a large extent was explained by the collapse in the agricultural sector in the early 1990's (Bakken et al, 2016a). Leng et al (2015) found that irrigation had a larger effect on lowflow than on high-flow of streams.…”
Section: Irrigationmentioning
confidence: 90%
See 1 more Smart Citation
“…Reservoirs in the upper part of the river basin can also be disadvantageous and pose a risk of operation to power producers in the lower parts of the basin. Upstream regulation might enable increased irrigation water withdrawals, hence reducing the power production, by its provision of regulated flow . In such cases, it would be unfair if downstream hydropower plants should carry parts of the burden of the upstream water losses if the reservoir is not beneficial.…”
Section: Dilemmas Related To the Applied Methodologymentioning
confidence: 99%